From lasik to smile: Time to change laser refractive surgery - Roberto Bellucci; Simonetta Morselli; Carlo Bellucci (Journal of Clinical Research and Ophthalmology - Peertechz Publications, 2021)
Purpose: To illustrate the advantages and limitations of Small Incision Lenticule Extraction (SMILE) over Laser Assisted Intrastromal Keratomileusis (LASIK) in the correction of myopia and myopic astigmatism. Materials and methods: The two procedures are analysed and compared for the technical aspects. While LASIK directly depends on the laser efficacy to get the refractive change, SMILE only depends on the computer ability to design the refractive lenticule. The loss in precision taking place in the peripheral cornea with LASIK is not possible with SMILE. Tissue consumption and postoperative dry eye are also lower with SMILE. Procedure abortion has less consequences with SMILE. From a clinical point of view, refractive and visual results with SMILE are similar as those of Wavefront Optimized and Wavefront Guided LASIK, but re-operations are easier after LASIK than after SMILE. Conclusion: When indicated, SMILE is better than LASIK from a technical and procedural standpoint and is equal to Wavefront Lasik as for the obtained results. LASIK is still more versatile and it is better for re-operations.